The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s13760-017-0786-7
|View full text |Cite
|
Sign up to set email alerts
|

Childhood hereditary ataxias: experience from a tertiary referral university hospital in Turkey

Abstract: Hereditary ataxias are a group of genetic disorders that are progressive and heterogeneous. The purpose of this study was to develop a practical and time-efficient approach to diagnosing childhood hereditary ataxias by analyzing characteristics and final diagnosis at a tertiary referral clinic for pediatric neurology. 196 patients admitted to the pediatric neurology department were included. The medical records were examined for demographic features, neurological, laboratory, electrophysiological, cranial imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Our previous study, based largely on cranial magnetic resonance imaging, laboratory and metabolic tests, muscle biopsy reports, and single limited gene studies also revealed a lower incidence of AT than anticipated. The rate of diagnosis of the autosomal recessive childhood ataxia was 19.9% in that study [7]. The majority of research into autosomal recessive ataxias has been European in origin, and there have been few studies from the Middle East and from our region in particular [7,11].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Our previous study, based largely on cranial magnetic resonance imaging, laboratory and metabolic tests, muscle biopsy reports, and single limited gene studies also revealed a lower incidence of AT than anticipated. The rate of diagnosis of the autosomal recessive childhood ataxia was 19.9% in that study [7]. The majority of research into autosomal recessive ataxias has been European in origin, and there have been few studies from the Middle East and from our region in particular [7,11].…”
Section: Discussionmentioning
confidence: 71%
“…The rate of diagnosis of the autosomal recessive childhood ataxia was 19.9% in that study [7]. The majority of research into autosomal recessive ataxias has been European in origin, and there have been few studies from the Middle East and from our region in particular [7,11].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…To the best of our knowledge, only one study has been reported among children with a broad spectrum of ARCAs in Turkey. Arslan et al [ 13 ] reported FRDA in five (12.8%) patients and AT in three (7.6%) in their study. We found FRDA in eight (25.8%) patients and AT in five (16.1%) patients.…”
Section: Discussionmentioning
confidence: 75%